Pathological risk factors for higher clinical stage in testicular seminomas. Issue 5 (14th August 2018) - Trevino, Karen E; Esmaeili‐Shandiz, Alaleh; Saeed, Omer; Xu, Huiping; Ulbright, Thomas M; Idrees, Muhammad T
Summary: Aims: Testicular seminomas require accurate staging for effective management. Twenty per cent are metastatic at presentation, while 80% are clinical stage I, requiring only orchiectomy and surveillance. Tumour size, rete testis invasion, hilar soft tissue invasion and lymphovascular invasion have been shown to incur a higher risk of metastasis and recurrence in clinical stage I seminomas, with little congruence between studies. Methods and results: We reviewed 211 cases of testicular seminomas and recorded patient age, tumour size, lymphovascular invasion and rete testis, hilar soft tissue, epididymis, spermatic cord, tunica albuginea and tunica vaginalis involvement. A univariate and multivariate analysis was performed comparing clinical stage I to advanced clinical stage patients (stages II and III) in reference to these factors. We found that tumour size ( P = 0.02), vascular invasion ( P = 0.02) and invasion of rete testis stroma ( P = 0.01), epididymis ( P = 0.02), spermatic cord ( P = 0.047) and hilar soft tissue ( P = 0.04) were predictors of higher clinical stage at the univariate level. However, multivariate analysis showed that only tumour size and vascular invasion remained significant ( P = 0.008 and 0.032, respectively). A tumour size of 4 cm was the cut‐off size found to be significant. Conclusions: Tumour size and vascular invasion are the strongest predictors of higher clinical stage in testicular seminomas. Our univariate data suggest that rete testis and hilar soft tissue invasion relate to higher clinical stage. However, neither of these factors were found to be independent risk factors at multivariate analysis. Therefore, this study supports tumour upstaging based only upon size and vascular invasion.